2008
DOI: 10.1002/tea.20264
|View full text |Cite
|
Sign up to set email alerts
|

Curricular orientations, experiences, and actions: Graduate students in science and mathematics fields work in urban high school classrooms

Abstract: We examined curricular orientations that graduate students in science and mathematics fields held as they experienced urban high‐school science and mathematics classrooms. We analyzed how these educators (called Fellows) saw themselves, students, teachers, schools, education, and the sense they made of mathematics and science education in urban, challenging settings in the light of experiences they brought with them into the project and experiences they designed and engaged in as they worked in classrooms for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 52 publications
1
2
0
Order By: Relevance
“…These understandings extend, we believe, previous research (Christodoulou & Varelas, 2009) with a different, larger set of similar Fellows (9 Fellows were studied), which has shown that when science and mathematics experts work in urban classrooms, subject matter and learning of the subject matter were not the only dominant considerations. Rather these Fellows privileged studentcenteredness of curriculum, instruction, and assessment, without, though, critically analyzing existing practices and policies.…”
supporting
confidence: 86%
“…These understandings extend, we believe, previous research (Christodoulou & Varelas, 2009) with a different, larger set of similar Fellows (9 Fellows were studied), which has shown that when science and mathematics experts work in urban classrooms, subject matter and learning of the subject matter were not the only dominant considerations. Rather these Fellows privileged studentcenteredness of curriculum, instruction, and assessment, without, though, critically analyzing existing practices and policies.…”
supporting
confidence: 86%
“…Concept formation or simply as conceptualization defined as one of transfer ways of learning except to knowledge representation, analogical reasoning, generalization and embodied cognition [4]. Outdoor learning facilitated student conceptualization of basic ecology concept included to graphing species density qualitatively, generating real food chain, describing either biotic and abiotic interaction or mutual biotic interaction (symbiosis) and creating potential solution for environmental problem.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, school ground is much popular and every day visited by student. [4]stated the learning process will be more effective if student was not participated in novice place for visit and related with daily living. A research by [5] suggests that learning biology in an outdoor environment has a positive cognitive impact.…”
mentioning
confidence: 99%